Standardization of Connor-Davidson Resilience Scale in Iranian subjects with Cerebrovascular Accident - Seyed Alireza Derakhshanrad1; Emily Piven3; Mehdi Rassafiani4; Seyed Ali Hosseini5; Farahnaz Mohammadi Shahboulaghi (Shiraz University of Medical Sciences, 2014)
Background: Resilience is a personal trait that can influence the stroke subjects' attitudes toward future opportunities and facilitate the transitional process and adaptation in them. Assessment of this trait in stroke subjects with a standardized tool would promote the rehabilitation protocols and occupational therapy interventions. Therefore, the objective of this study was to standardize the Connor-Davidson Resilience Scale (CD-RISC) for Persian Iranian people who have had strokes. Methods: A descriptive observational study was adopted in order to standardize the CD-RISC in stroke population. The population was comprised of 34 female and 29 male subjects with a mean age of 51.4±10.6 years and the history of ischemic or hemorrhagic cerebrovascular accidents. Subjects were recruited based on inclusion criteria within the period of two months between May and July of 2014. Descriptive statistics were calculated along with the Cronbach's alpha to determine reliability. Standard multiple regression analyses searched for any correlation between variables and resilience. Results: Statistical parameters revealed a mean of 58.4±15.5 for CD-RISC raw scores. Percentile ranks were also calculated from raw data. Cronbach's alpha of 0.892 revealed that the CD-RISC had high reliability for the population of this study. Multiple regression analyses showed that the functional status was the only variable that uniquely predicted subjects' resilience (ß=0.41; P<0.01). Conclusion: The findings of this research confirmed applicability of CDRISC in Iranian people who have had strokes. The standardized CD-RISC was determined to be suitable for use in the clinic and for utilization in research studies in Iranian people status post-stroke.